Pengaruh Customer Perceived Value dan Switching Barriers Terhadap Customer Retention - Pipih Sopiyan (Coopetition : Jurnal Ilmiah Manajemen, 2021)
The purpose of this study was to determine the effect of Customer Perceived Value and Switching Barriers on Customer Retention with the research object of Majalengka University students using IM3 Ooredoo Cards. This research is a type of survey research with descriptive and verification approaches with a sample size of 100 students. The data source was obtained from primary data where data was taken directly from students, namely through filling out a questionnaire with a Likert scale measurement. Data analysis through multiple regression analysis, coefficient of determination, t test and f test. The results showed that Customer Perceived Value has a positive and significant effect on Customer Retention with a contribution rate of 21.71%. Switching Barriers have a positive and significant effect on Customer Retention with a contribution rate of 21.62%. Customer Perceived Value and Switching Barriers have a positive and significant effect on Customer Retention with a contribution rate of 28.8%. For further research, it is important to conduct research related to customer lifetime value with 2-3 research objects and to use more complex analytical tools.